Psychosocial incidence of single mothers at the State Technical University of Quevedo 2023 - Villamar Gavilanes, Angie Dayana, MSc; Saldarriaga Jiménez, Dolores Guadalupe, MSc; Bajaña Mendieta, Inés de la Luz, MSc; Acurio Barre, Solange Lisseth, MSc; Romero Segovia, Cristian Armando, MSc (International Journal of Medical Toxicology and Legal Medicine, 2024)
Being a single mother by one’s own choice or due to certain circumstances leads to fulfilling some responsibilities around household management, raising children, work and academic activities, among others. Objective: To determine the psychosocial incidence on single mothers at the Technical University of Quevedo, 2023. Methodology: An observational, mixed, descriptive, correlational, cross-sectional, and field design was used. The population was 143 people, including students and teachers for the quantitative modality and 5 single mothers for the qualitative collection. The technique for collecting data was the survey and the interview, each with its questionnaire (quantitative instrument: 33 questions; qualitative instrument: 13 questions). Results: In psychosocial factors, they decide to be a single mother because their partner abandons them (48.9%), they can make decisions more freely (39.9%), as a social disadvantage it can generate emotional conflicts for their child when growing up (23.1%), they take on a lot of responsibility alone (32.2%), socially the single mother is criticized (47.6%) and they support this decision (93.0%); the role of single mother within their family group, they were single mothers (40.6%), they think that this decision is okay (76.9%), it decreases their will to face day to day (27.3%), role of guest when living with their parents (42.7%) and occupies the role of father and mother when living alone (80.4%); in the work area, equal remuneration than another woman (60.1%), equal rights (53.1%), there may be inefficiency because they do not have anyone to leave their child with (46.9%) and the role is professional (33.6%); and in the emotional state, they will have fixed worries about their future (49.0%), a feeling of admiration and respect (89.5%), and they feel completely happy when their children achieve success and happiness (75.5%). Conclusion: Single motherhood or being a single mother is a relevant reality in society, associated with several challenges that compromise the psychosocial state of the mother and her child.